2003
DOI: 10.1029/2003jd003507
|View full text |Cite
|
Sign up to set email alerts
|

Asian outflow and trans‐Pacific transport of carbon monoxide and ozone pollution: An integrated satellite, aircraft, and model perspective

Abstract: [1] Satellite observations of carbon monoxide (CO) from the Measurements of Pollution in the Troposphere (MOPITT) instrument are combined with measurements from the Transport and Chemical Evolution Over the Pacific (TRACE-P) aircraft mission over the northwest Pacific and with a global three-dimensional chemical transport model (GEOS-CHEM) to quantify Asian pollution outflow and its trans-Pacific transport during spring 2001. Global CO column distributions in MOPITT and GEOS-CHEM are highly correlated (R 2 = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
258
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 220 publications
(278 citation statements)
references
References 48 publications
20
258
0
Order By: Relevance
“…[42] The model reproduces fairly well the vertical profiles of CO observed in the two regions (correlation coefficient > 0.8, Figure 3), but underestimates the observed concentrations in the boundary layer both in the northern and southern regions (mean absolute bias by 13% and 17%, respectively), which may be due to too low anthropogenic and biomass burning emissions in eastern Asia, as indicated also by previous evaluations of the TRACE-P campaign [e.g., Heald et al, 2003;Allen et al, 2004]. We find a correlation coefficient of 0.59 and 0.83 between simulated and observed NO and NO 2 concentrations, respectively.…”
Section: Evaluation Of the Simulated Distributions Of Trace Gas And Asupporting
confidence: 55%
“…[42] The model reproduces fairly well the vertical profiles of CO observed in the two regions (correlation coefficient > 0.8, Figure 3), but underestimates the observed concentrations in the boundary layer both in the northern and southern regions (mean absolute bias by 13% and 17%, respectively), which may be due to too low anthropogenic and biomass burning emissions in eastern Asia, as indicated also by previous evaluations of the TRACE-P campaign [e.g., Heald et al, 2003;Allen et al, 2004]. We find a correlation coefficient of 0.59 and 0.83 between simulated and observed NO and NO 2 concentrations, respectively.…”
Section: Evaluation Of the Simulated Distributions Of Trace Gas And Asupporting
confidence: 55%
“…The scaled GEIA emissions for East Asia are consistent with TRACE-P aircraft observations in Asian outflow in 2001 (Heald et al, 2003), but NO x emissions in East Asia have grown rapidly since then (Zhang et al, 2007, Zhang et al, 2008. We also conducted a simulation using an (Zhang et al, 2007).…”
Section: Model Descriptionsupporting
confidence: 50%
“…Three primary mechanisms can loft pollutants from the boundary layer to the free troposphere: (1) airstreams such as the warm conveyor belt (WCB) that are associated with middle latitude cyclones (Bey et al, 2001;Cooper et al, 2002;Hannan et al, 2003;Kiley and Fuelberg, 2006), (2) orographic lifting (Henne et al, 2004;Chen et al, 2009;Ding610 C. A. Klich and H. E. Fuelberg: Transport of CO in a middle latitude cyclone latitudes (Stohl et al, 2002), distinct maxima are located off the east coasts of North America and Asia (Stohl, 2001;Eckhardt et al, 2004). The long-range synoptic-scale WCBrelated transport of atmospheric pollutants has been studied across both the Pacific Ocean (e.g., Jaffe et al, 1999;Yienger et al, 2000;Bey et al, 2001;Carmichael et al, 2003;Heald et al, 2003;Jacob et al, 2003;Liu et al, 2003;Cooper et al, 2004) and Atlantic Ocean (Stohl and Trickl, 1999;Cooper et al, 2001Cooper et al, , 2002Naja et al, 2003;Li et al, 2005;Fehsenfeld et al, 2006;Singh et al, 2009). Anthropogenic emissions across eastern Asia have been increasing rapidly (Richter et al, 2005;Ohara et al, 2007;Zhang et al, 2007Zhang et al, , 2009, and their transport to the western United States (US) has been shown to increase local surface ozone concentrations Fiore et al, 2002;Jaffe et al, 2004;Oltmans et al, 2008;Zhang et al, 2008;Reidmiller et al, 2009;…”
Section: Introductionmentioning
confidence: 99%